Pertumbuhan In Vitro Tiga Varietas Krisan Pada Variasi Media Murashige & Skoog (MS) - Kaurow, Tamariska Julita; Mandang, Jeany; Mamarimbing, Rinny (Sam Ratulangi University, 2023)
This study aims to determine the growth of three Chrysanthemum varieties on complete MS media, 50% MS and 50% MS which were given coconut water through In vitro culture. This research was conducted from March to May 2022 at the Tissue Culture Laboratory, Faculty of Agriculture, Sam Ratulangi University, Manado. This study used a factorial design in a completely randomized design (CRD) with 2 treatment factors, namely media and varieties consisting of 9 treatments and 4 replications so that a total of 36 bottles, namely MS 100%, MS ½ (MS 50%), MS ½ AK (MS 50% + coconut water 200 ml/l). The variables observed were: plant height, number of leaves, fresh weight, and number of roots. The results of the study showed that the average growth of the 3 Chrysanthemum varieties was better on ½ MS and ½ MS media supplemented with coconut water. The best wet weight on ½ MS+AK media corresponds to the highest number of roots in the same treatment.